High-intensity interval training in the prehabilitation of cancer patients—a systematic review and meta-analysis - Palma, Stefano; Hasenoehrl, Timothy; Jordakieva, Galateja; Ramazanova, Dariga; Crevenna, Richard (Supportive care in cancer, 2021)
Purpose To evaluate the impact of high-intensity interval training (HIIT) on health-related outcome parameters in the prehabilitation of patients diagnosed with cancer. Methods A systematic review and meta-analysis of comparative studies on HIIT in cancer prehabilitation conducted by screening standard databases from their inception to March 30, 2020. Outcomes of interest included cardiorespiratory fitness, feasibility, safety, clinical, and patient-reported outcomes. Results Of the 855 identified studies, 8 articles met the inclusion criteria (7 randomized, 1 non-randomized controlled trial) with a total of 896 patients. The study protocols were heterogeneous, but the methodological quality ranged from good to high according to PEDro scale. Meta-analysis revealed a significant improvement of peak oxygen consumption (VO 2 peak) achieved with HIIT compared to usual care. Furthermore, HIIT was feasible and safe, showing low risk of adverse events and positive effects on health-related outcomes in prehabilitative settings. Conclusion In the phase of prehabilitation, HIIT has potential health benefits in patients diagnosed with cancer and is feasible and safe to perform. Nonetheless, larger randomized controlled trials focusing on long-term effects (such as cancer recurrence or survival rates) are missing, to underline the potential relevance of HIIT for cancer patients.